ANALISIS PENDAPATAN USAHATANI PADI DI KECAMATAN KURANJI KOTA PADANG SUMATERA BARAT - Angelia Leovita; Ilham Martadona (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2021)
The food crops sub-sector is an important and strategic sector because it supports the life of the Indonesian people where the main staple food is rice. The purpose of the study was to determine (1) the production costs in rice farming, (2) the income of rice farming and (3) the amount of return to labor in rice farming. This study uses quantitative data analysis. Sampling technique with snowball sampling technique with the number of respondents 30 people. The results showed that (1) the total production cost of rice farming was Rp. 9,254.112.80, (2) The amount of income from rice farming was Rp. 3,694,373.38, farming is feasible and economically profitable to implement because the value of R/C of 1.40 and (3) the return to labor earned is greater than the wages paid for labor.